Diseño de un modelo de responsabilidad social empresarial en la óptica del trabajador, la sociedad y el medio ambiente aplicado a la empresa UMA Creativa - DM Quito - Calvas Guerra, Deysi Tamara (2015)
Corporate Social Responsibility recently has become a new form of management and doing business in which the company ensures that its operations are sustainable in economic, social and environmental. This is an issue of great global impact that aims to achieve sustainable development to bring the commitment of the company to identify gaps and provide solutions, and in this way anneal what are the interests of different stakeholders with which the company relates and have a vision focused on respect for life, people, values, ethics, community and environment in which it operates. The Corporate Social companies is essentially a voluntary arrangement concept contribute to a better society and a cleaner environment demonstrating development and mutual integration between business and society, and create a positive impact. In Ecuador the implementation of CSR in business is a little known subject, and the application is done by a small number of companies, creative Uma wants to implement these policies in order to make a commitment to work with the principles of Corporate Social Responsibility. In this research a model of Corporate Social Responsibility for Uma creative company, to implement strategic and policies for the benefit of workers, contribution to the community and care for the environment was developed.